Incompliance of total hip arthroplasty (THA) patients to limited weight bearing - Schäfer, Anja; Hotfiel, Thilo; Pauser, Johannes; Swoboda, Bernd; Carl, Hans-Dieter (Archives of Orthopaedic and Trauma Surgery, 2015)
Limited weight bearing of the lower extremity is a commonly applied procedure in orthopedic rehabilitation following trauma surgery and joint replacement. The compliance of patients with limited weight bearing after cementless total hip arthroplasty has not yet been surveyed using sensor-loaded insoles. The objective of this study was to investigate foot loadings in patients after THA under the assumption of limited weight bearing.Peak pressures for the hindfoot, midfoot and forefoot were obtained from 14 patients (10 women, 4 men, age 63 ± 12 years, height 172 ± 9 cm, weight 92 ± 20 kg, BMI 31 ± 6 kg/m(2)) by means of dynamic pedobarography, with full weight bearing preoperatively (baseline) and at 8-10 days after cementless total hip arthroplasty, walking again on even floor, and also walking upstairs and downstairs with a restriction of weight bearing to 10 % body weight, taught by an experienced physiotherapist with a bathroom scale.Foot loadings with limited weight bearing on even floor remained up to 88 % from full weight bearing preoperatively. Walking upstairs and downstairs under the same condition was approximately equal to a bisection of peak pressures from full weight bearing.Patients following cementless do not comply with limited weight bearing when they are trained by the use of a bathroom scale.
EVALuna2:10901